LEGAL PROTECTION FOR CHILDREN WHO COMMIT MOTORCYCLE THEFT DURING THE INVESTIGATION PROCESS - Gunawan Widjaja; Dimas Tripraditiya (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Children are part of the younger generation, a human resource that represents the potential and future of the nation's aspirations. The recent social reality in society is the issue of behavioural deviations among children, and more than that, there are children who commit unlawful acts, particularly motorbike theft. The issues discussed are: 1) What form of legal protection is available for children who  and 2)  What obstacles do the police face in implementing legal protection for children who commit motorbike theft? Based on the author's observations on the chosen topic, it is concluded that legal protection for children who commit the crime of motorcycle theft in the investigation process emphasises special handling that considers the psychological condition and maturity of the child. The investigation process must ensure that the rights of children are protected, including the right to be heard, assisted by parents or guardians, and protected from violence or torture. Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA) regulates the procedures for handling children who commit crimes, including in the investigation process.